2014
DOI: 10.1177/0954406214533529
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies for wind turbine’s shrink disk

Abstract: With the wide application of multi-layer interference fit in many engineering fields, as for key component in the wind turbine generator, wind turbine’s shrink disk uses interference fit to transmit rated torque and axial force. In order to ensure the work reliability of shrink disk during the actual operation, the paper presents a more precise method on the design calculation of contact pressure on the mating surfaces with interference fit. In accordance with the order from the inside to the outside, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Yuan 16 constructed a stress analysis model for shrink-fit high-pressure vessels based on MTCT. Wang et al 17 and Jianmei et al 18 simplified the wind turbine shrinking disk into a multi-layer interference component, and deduced the matrix expression of combined pressure and interference magnitude by analyzing the geometric relationship of the multi-layer interference component using MTCT. However, the above analysis is based on the plane strain hypothesis, which can not realize the analysis of stress concentration at the mating boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan 16 constructed a stress analysis model for shrink-fit high-pressure vessels based on MTCT. Wang et al 17 and Jianmei et al 18 simplified the wind turbine shrinking disk into a multi-layer interference component, and deduced the matrix expression of combined pressure and interference magnitude by analyzing the geometric relationship of the multi-layer interference component using MTCT. However, the above analysis is based on the plane strain hypothesis, which can not realize the analysis of stress concentration at the mating boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Interference fit is a main assembly mode, which is widely applied in the shaft sleeve parts due to good stability and simple structure [1,2]. Considering the safety and costs, some key interference fit parts need regular overhaul and maintenance, such as the rubber joint of the train's bogie.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies are found on the design calculation of contact pressure on the mating surfaces with interference fit for wind turbines neglecting the rotational loading effect. 30 , 31 Kamal 5 , 11 has carried out the analysis of residual stresses in the rotational autofrettage of disks, albeit by treating the disk to be rotating freely. Although the free rotation of the disk is a good approximation for the analysis of rotational autofrettage; however, rotating a disk freely is a practically challenging task.…”
Section: Introductionmentioning
confidence: 99%